Flexible three-dimensional anticounterfeiting plasmonic security labels : utilizing z-axis-dependent SERS readouts to encode multilayered molecular information - Liu, Yejing (2020)
Current surface-enhanced Raman scattering (SERS)-based anticounterfeiting strategies primarily encode molecular information in single two-dimensional (2D) planes and under-utilize the three-dimensionality (3D) of plasmonic hot spots. Here, we demonstrate a 3D SERS anticounterfeiting platform, extending "layered security" capabilities from 2D to 3D. We achieve this capability by combining 3D candlestick microstructures with 3D hyperspectral SERS imaging to fully resolve at least three layers of encoded information within the same 2D area along the z-axis, notably using only a single probe molecule. Specific predesigned covert images can only be fully recovered via SERS imaging at predetermined z values. Furthermore, our 3D SERS anticounterfeiting security labels can be fabricated on both rigid and flexible substrates, widening their potential usages to curved product surfaces and banknotes.